Seasonal and latitudinal variation in seagrass mechanical traits across Europe: The influence of local nutrient status and morphometric plasticity. (7th July 2017) - Soissons, L. M.; van Katwijk, M. M.; Peralta, G.; Brun, F. G.; Cardoso, P. G.; Grilo, T. F.; Ondiviela, B.; Recio, M.; Valle, M.; Garmendia, J. M.; Ganthy, F.; Auby, I.; et al.
Abstract: Seagrasses are marine flowering plants distributed worldwide. They are however threatened, mostly due to the increase of human activities. Seagrasses have the capacity to adapt their morphological, physiological, and mechanical traits to their local conditions. Mechanical traits have been identified as a good tool to investigate a plant‐species capacity to withstand physical forces or disturbances but are still sparsely studied in seagrasses. With this study, we aimed to assess how the mechanical traits of a broadly spread seagrass species vary along a latitudinal gradient in relation to its morphometric plasticity and nutrient status. We found that seagrasses acclimate their mechanical traits in relation to their physiological or morphological traits, both over the growing season and across a latitudinal range: leaves were weaker and thinner in northern areas, particularly at the end of the growing season. Besides the influence of the latitudinal gradient, leaf mechanical strength and stiffness were both strongly affected by their morphometric plasticity. Moreover, we showed that leaves mechanical traits change depending on their nutrient status: leaves were stronger and stiffer in oligotrophic conditions as compared to more eutrophic conditions. Thus, our results imply that, under eutrophication, leaves become weaker and thus more vulnerable to physical forces. This vulnerability is higher in the north at the end of the growing season. The latter is consistent with the more ephemeral character of northern seagrass meadows, in contrast to the more evergreen southern meadows.